2019
DOI: 10.1038/s41467-019-08533-2
|View full text |Cite
|
Sign up to set email alerts
|

BMP-dependent synaptic development requires Abi-Abl-Rac signaling of BMP receptor macropinocytosis

Abstract: Retrograde BMP trans-synaptic signaling is essential for synaptic development. Despite the importance of endocytosis-regulated BMP receptor (BMPR) control of this developmental signaling, the mechanism remains unknown. Here, we provide evidence that Abelson interactor (Abi), a substrate for Abl kinase and component of the SCAR/WAVE complex, links Abl and Rac1 GTPase signaling to BMPR macropinocytosis to restrain BMP-mediated synaptic development. We find that Abi acts downstream of Abl and Rac1, and that BMP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 67 publications
(115 reference statements)
2
29
0
Order By: Relevance
“…Synaptic pMad is likely part of a complex system involving receptor dynamics and endosomal processing/shuttling, that ‘tags’ axonal branches for growth, maturation, and plasticity. The molecular mechanisms known to regulate local BMP signaling in presynaptic boutons are diverse: the dynamics of nuclear importins, interactions with other trans‐synaptic and cytoplasmic signaling systems, recycling of BMP receptors through endocytic and endosomal regulation, RNA binding protein activity, phospholipid composition, and cytoskeletal regulation (Banerjee & Riordan, ; Banerjee, Venkatesan, & Bhat, ; Deshpande et al, ; Eaton & Davis, ; Fuentes‐Medel et al, ; Heo et al, ; Higashi‐Kovtun et al, ; Huang et al, ; Kim et al, ; Li et al, ; Liu et al, ; Merino et al, ; Piccioli & Littleton, ; Politano et al, ; Sulkowski et al, ; Summerville et al, ; Vanlandingham et al, ; Zhang et al, ; Zhao et al, ). Local, retrograde effects are also possible through muscle‐specific regulation of glutamate receptor composition and Gbb production/release (this study; also see Halstead et al, ; Sulkowski et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic pMad is likely part of a complex system involving receptor dynamics and endosomal processing/shuttling, that ‘tags’ axonal branches for growth, maturation, and plasticity. The molecular mechanisms known to regulate local BMP signaling in presynaptic boutons are diverse: the dynamics of nuclear importins, interactions with other trans‐synaptic and cytoplasmic signaling systems, recycling of BMP receptors through endocytic and endosomal regulation, RNA binding protein activity, phospholipid composition, and cytoskeletal regulation (Banerjee & Riordan, ; Banerjee, Venkatesan, & Bhat, ; Deshpande et al, ; Eaton & Davis, ; Fuentes‐Medel et al, ; Heo et al, ; Higashi‐Kovtun et al, ; Huang et al, ; Kim et al, ; Li et al, ; Liu et al, ; Merino et al, ; Piccioli & Littleton, ; Politano et al, ; Sulkowski et al, ; Summerville et al, ; Vanlandingham et al, ; Zhang et al, ; Zhao et al, ). Local, retrograde effects are also possible through muscle‐specific regulation of glutamate receptor composition and Gbb production/release (this study; also see Halstead et al, ; Sulkowski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A direct effect of Gbb on BMP receptor expression, perdurance, or signaling has not yet been described. However, Gbb signaling influences macropinocytosis in vitro, and this process does influence the expression of a type I BMP receptor (Kim et al, ). It is also unknown whether retrograde Gbb signaling influences the delivery or release of Gbb from motoneurons, which has striking effects on NMJ growth (James & Broihier, ; James et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Abi, a protein subunit of the Scar/WAVE complex, localises in macropinocytic vesicles during synaptic development in Drosophila melanogaster. Upon phosphorylation by Abl kinase, Abi is thought to regulate Rac1 Scar/WAVEmediated actin assembly [72]. PI3K is also important for macropinosome formation by converting PI4,5P 2 into PI3,4,5P 3 , which somehow defines regions/boundaries of the macropinosome and enables membrane protrusion extension.…”
Section: Pressures Driving Migration: Starvation For Nutrients and Mamentioning
confidence: 99%
“…Here we provide the first quantitative analysis of the composition and dynamics of individual presynaptic F-actin structures. Numerous studies have examined actin dynamics at the level of entire synapses or qualitatively described dynamics of discrete actin structures (Bloom et al, 2003;Colicos et al, 2001;Nunes et al, 2006;Piccioli and Littleton, 2014;Sankaranarayanan et al, 2003;Zhao et al, 2013), and identified diverse roles for actin, including synaptic vesicle endocytosis (Holt et al, 2003;Kononenko et al, 2014;Soykan et al, 2017;Watanabe et al, 2013;Wu et al, 2016;Zhao et al, 2013), synaptic vesicle organization and mobilization (Guzman et al, 2019;Lee et al, 2012;Marra et al, 2012;Owe et al, 2009;Sakaba and Neher, 2003;Wolf et al, 2015), active zone organization and function (Boyl et al, 2007;Morales et al, 2000;Wagh et al, 2015;Waites et al, 2011;Wang et al, 1999), and receptormediated endocytosis (Kim et al, 2019;Rodal et al, 2008). Bulk analyses, which do not separate individual dynamic actin structures in space and time, are limited in their ability to discern how the regulation and dynamics of actin contribute to these distinct functions.…”
Section: The Predominant Presynaptic Actin Structures Resemble Endocymentioning
confidence: 99%